PEMBERIAN BEBERAPA ZPT ORGANIK TERHADAP BEBERAPA VARIETAS BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE-NURSERY - Yazid Habiby Lubis; Mita Setyowati; Aboe B. Saidi (Universitas Teuku Umar, 2019)
The aims of this study was to determine the effect of several organic growth regulatory on several varieties of oil palm seedlings (Elaeis guineensis Jacq) in Pre Nursery. The research was carried out in the experimental garden of the Faculty of Agriculture, Teuku Umar University, West Aceh, from March until finished. The materials used were Organic growth regulatory in the form of 50 cc coconut water, 50 cc union extract and 50 cc bamboo shoot extract. While the varieties of oil palm seedlings are varieties that yangambi, simalungun and 239 from IOPRI Medan. This study used a factorial randomized block design (RBD) 4 X 3 with 3 replications. Giving growth regulatory (Z) consists of 4 levels, namely: Z0 = Control, Z1 = Coconut water, Z2 = Shallot Extract, Z3 = Bamboo Extract, while Variety factor (V) consists of 3 levels: V1 = Yangambi, V2 = Simalungun, V3 = 239. Observation parameters are increase in seedling height (cm), stem diameter (mm), number of leaf midribs (midrib), wet stover weight (g), number of roots (number) and root length (cm). Keywords: Growth Regulatory, Varieties, Oil Palm, Pre Nursery